Nocturna - Motayne, Maya (2019)
"To Finn Voy, magic is two things: a knife to hold under the chin of anyone who crosses her...and a disguise she shrugs into as easily as others pull on cloaks. As a talented faceshifter, Finn hasn't seen her own face in years, and that's exactly how she likes it. But when she gets caught by a powerful mobster, she's forced into an impossible mission: steal a legendary treasure from Castallan's royal palace or be stripped of her magic forever. After the murder of his older brother, Dezmin, Prince Alfehr is first in line for the Castallan throne. But he can't help feeling that he will never live up to this brother's legacy. Riddled with grief, Alfie is obsessed with finding a way to bring Dez back, even if it means dabbling in forbidden magic. But when Finn's and Alfie's fates collide, they accidentally unlock a terrible, ancient power--which, if not contained, will devour the world. And with Castallan's fate in their hands, the two must race to vanquish what they have unleashed, though it will mean facing the deepest darknesses in their pasts."--Dust jacket flap
Series information from Goodreads.com
Map on endpages
"A faceless thief. A desperate prince. A darkness unleashed" -- Front jacket cover
Keywords: Magic -- Fiction; Relics -- Fiction; Princes -- Fiction; Brigands and robbers -- Fiction; Shapeshifting -- Fiction; Young adult works; Juvenile works; Fantasy fiction; Fiction; Fantasy fiction; Fantasy fiction